A case study exploring entrepreneurial resilience in Durban, South Africa - Reddy, Menokin (The IIE, 2017)
South Africa is currently experiencing a high level of unemployment, and entrepreneurship is regarded as a tool that can help solve the problem (Business Tech, 2017). Resilience is believed to influence a person’s course of action and is considered to be one of the motivating factors that are necessary for entrepreneurship. With this in mind, the persistent question is how do entrepreneurs motivate themselves after failure? Data was collected using a semi-structured interview approach as it enabled the researcher to explore the views, experiences and beliefs of the participants on specific matters thus providing the researcher with a deeper understanding of the phenomenon. The study found that perseverance and a positive mindset are prominent components that contribute to entrepreneurs staying motivated even after experiencing failure. Furthermore, the study found that all participants had a desire to be in control of their destiny. Recommendations were made for future researchers to increase the sample size so more rigorous data could be generated. It was also recommended that entrepreneurial resilience is analysed across the country, but more specifically in Johannesburg, as it has the most entrepreneurs in South Africa (Statistics South Africa, 2017).
Keywords: Unemployment; Entrepreneurship; Motivation; Entrepreneurial resilience